Analisis efisiensi pemasaran timun apel di Desa Tanjung Pakis, Kecamatan Pakis Jaya, Kabupaten Karawang - Cindy Sofia; Sulandjari, Kuswarini; Suhaeni (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
Apple cucumber, an annual horticultural crop, is primarily cultivated in the coastal area of Tanjung Pakis Village, Karawang Regency, which serves as a significant production center for this crop. These cucumbers, which are a hybrid of cucumber and melon plants, remain relatively unknown in Karawang due to limited marketing and a small number of farmers involved. The research aims to explore the marketing channels and their effectiveness in the apple cucumber supply chain. The study included a sample of 20 farmers selected through Census Sampling, alongside 2 middlemen, 1 wholesaler, and 7 retailers identified using Snowball Sampling. Primary data was collected via questionnaire-based interviews, complemented by secondary data from sources like BPS, the Agriculture Office, and the Tanjung Pakis Village Office. Analysis focused on revenue, profit margins, farmer's share, and overall marketing efficiency. Results identified four distinct marketing patterns: Channel I (Farmers-Middlemen-Wholesalers-Consumers), Channel II (Farmers-Middlemen-Retailers-Consumers), Channel III (Farmers-Wholesalers-Consumers), and Channel IV (Farmers-Retailers-Consumers). Notably, Channel IV emerged as the most efficient, characterized by the lowest marketing margin of Rp. 5,000/kg, a farmer's share exceeding 66.67% (indicating efficiency), and a marketing efficiency ratio of 0.08 (EP < 1 indicating efficiency). These findings underscore the potential for optimizing apple cucumber marketing strategies to enhance profitability and promote wider adoption among farmers in the region.